1048. Beta-Hemolytic Streptococcal Infective Endocarditis: Characteristics and Outcomes From a Large, Multi-National Cohort. (26th November 2018) - Fernandez-Hidalgo, Nuria; Gharamti, Amal; Aznar, María Luisa; Chu, Vivian H; Rizk, Hussein; Kanafani, Zeina
Abstract: Background: β-Hemolytic streptococci (BHS) are an uncommon cause of infective endocarditis (IE). The aim of this study was to describe the clinical features and outcomes of patients with β-hemolytic streptococcal infective endocarditis in a large multi-national cohort, and compare them to patients with oral Viridans IE, a more common cause of IE. Methods: The International Collaboration on Endocarditis Prospective Cohort Study (ICE-PCS) is a large multi-national database that recruited patients with IE prospectively using a standardized data set. Sixty-four sites in 28 countries reported patients prospectively using a standard case report form (CRF) developed by ICE collaborators. Patients with BHS IE were compared with patients with IE due to Oral Viridans Streptococci (OVS). Results: Among 1336 cases of streptococcal IE, 823 (62%) were caused by OVS and 147 (11%) by BHS. The majority of patients in both groups belonged to the male gender and had similar median age. Among the predisposing conditions, congenital heart disease and native valve predisposition were more commonly associated with OVS IE than with BHS IE ( P < 0.005). The presence of endocavitary cardiac device is associated more with BHS IE than with OVS IE ( P = 0.026). BHS were more likely to be penicillin-susceptible than OVS ( P = 0.001). Clinically, patients with BHS IE are more likely to present acutely ( P < 0.005) and with fever ( P = 0.024). BHS IE is more likely to be complicated by stroke ( P < 0.005) and other systemic embolism ( P < 0.005). The overall in-hospital mortality of BHS IE was significantly higher than that of OVS IE ( P = 0.001). The independent factors associated with in-hospital mortality for β-hemolytic streptococcal IE were age, per 1-year increment (OR 1.044; CI 1.014–1.075; P = 0.004) and prosthetic valve IE (OR 3.029; CI 1.171–7.837; P = 0.022). The complications associated with a higher in-hospital mortality were CHF (OR 2.513; CI 1.074–5.879; P = 0.034), especially CHF NYHA III or IV (OR 4.136; CI 1.707–10.025; P = 0.002), and stroke (OR 3.198; CI 1.343–7.619; P = 0.009). Conclusion: Our findings suggest that BHS IE is an aggressive disease characterized by an acute presentation. It is associated with a significant rate of complications and a high rate of in-hospital mortality. This underlines the importance of early surgery to prevent the progression of disease. Disclosures: All authors: No reported disclosures.